Carolina Maria de Jesus e Clarice Lispector: representações do feminino na literatura brasileira contemporânea - Macena, Fabiana Souza Valadão de Castro (2017)
The present work has as objective to analyze the texts Quarto de Despejo (1960) and Onde estaes felicidade? (2014) by Carolina Maria de Jesus as also Perto do Coração Selvagem (1998) and Amor (1998) by Clarice Lispector. From the comparative studies of Tânia Carvalhal (2006), we try to establish a dialogue between these two authors and some of their texts, in order to consider how female participation in literary production interferes in the representation of women (Butler, 2017). The course of analysis includes the ethnic, social and cultural aspects that affect writing and, consequently, create points of dissonance between these two authors, while convergence stems from the possibility of a woman to represent herself. In the process of writing, women emerge the anxieties, conflicts and longings proper to their universe; this means the opportunity for the subaltern to represent himself and, in this sense, conscious of his voice, to be empowered (LÉON, 2001). Thus, it is hypothesized that women's writing will reverberate the social, cultural and ethnic conditions to which the woman was and is submitted, allowing a comparison that reflects on the path taken by this gender in the attempt to leave the periphery and goes forward the conquest of an “own roof" (WOOLF, 2004). If in the text of Clarice Lispector, the flow of consciousness and the existential dimension prevail, there being room for the expansion and evaluation of feelings such as love; in Carolina Maria de Jesus’ writing hatches the material aspect, represented in incipient necessities like children’s education, the lack of money and food that will culminate in the degradation of the individual without perspectives. In order to observe and contrast the writing of these two authors, it is necessary to recognize the ethnic elements studied by Regina Dalcastagnè (2012), to use the social and identity studies proposed by Stuart Hall (2015) and to analyze the cultural analyzes of Pierre Bourdieu (2012) and Simone de Beauvoir (1980), observing the influence of these markers in the writing process. The Claricean text enjoys the privilege that comes from an educated woman, admitted in the niche of the intellectuality, while the Carolinean production arises under the same marginalization suffered by the author. In short, through the analysis, it can be seen that the woman in the text of Clarice Lispector may not get rid of the social and cultural domination that has been pursuing her for centuries, however, she begins to have a small right over her body and to reflect about her desires. Although in more arid soil, it is in the same emancipatory sense that goes through Carolina Maria de Jesus, who, under the prejudice of being a woman, without a husband, with no schooling, money or professionalization, realizes the dream of becoming a writer and opens space for other voices, subalternized like hers, to be heard and considered in the social and literary space.